The Role of Agriculture in Climate Change: A Global Perspective - Balogh, Jeremiás Máté (International Journal of Energy Economics and Policy, 2020)
Nowadays, the topic of climate change and its consequences are on the agenda of the everyday life. Due to the greenhouse effect, an effective doubling of CO2 concentrations is expected by 2030. During the history, the concentration of greenhouse gases in the atmosphere has grown mainly as a result of human activity in the Earth. The anthropogenic CO2 emission accounts for around three-fourths of global GHG emissions. The development of greenhouse gas emissions is extremely associated with global warming. Approximately one-third of the global atmospheric methane emissions derived from agricultural activities. Throughout the agricultural production process, high amounts of GHG emissions are released, which affect negatively the environment and the climate. The intensity of agriculture-related factors of climate change is varying over countries and continents. The objective of the research is to explore the main agricultural-related determinants of climate change focusing on livestock, burning crop residues, rice production, manure management, synthetic fertilizer use along with the geographical and cultural factors of the pollution. The analysis was carried out on a sample representing the world economy. Keywords: carbon dioxide emission, agricultural production, trade, language, geography, world JEL Classifications: Q10, Q54, Q56 DOI: https://doi.org/10.32479/ijeep.8859